Correlational Study of Self-Efficacy and Social Withdrawal among Secondary School Adolescents - Taiye Hassan AHMED; Habibat Bolanle ABDULKAREEM; Kamil Adekola LASISI (LPPM Undiksha, 2025)
A proportion of secondary school adolescents exhibit social withdrawal behaviors characterized by low levels of social interaction, school participation, and self-confidence. This study aims to analyze the relationship between self-efficacy and social withdrawal among secondary school adolescents. A quantitative approach with a descriptive correlational survey design was employed. The research population comprised 92,097 senior high school students, with a sample of 398 students selected using the Slovin formula and purposive sampling technique. Data were collected using the Social Self-Efficacy Scale (SSES) and the Social Withdrawal Frequency Scale (SWFS). Data analysis was conducted using Pearson Product–Moment correlation and multiple linear regression analysis. The results indicate that low self-efficacy shows a positive but non-significant relationship with social withdrawal, whereas moderate and high self-efficacy demonstrate weak and non-significant negative relationships with social withdrawal. Furthermore, both the simultaneous and partial contributions of self-efficacy to social withdrawal were not statistically significant. The findings suggest that although self-efficacy is not a strong predictor of social withdrawal, strengthening self-efficacy remains important as a preventive effort to support adolescents’ social adjustment through school guidance and counseling services. This study concludes that despite a tendency toward a relationship between self-efficacy and social withdrawal, the association is not statistically significant. The implications of this study highlight the important role of school counselors in identifying students with low self-efficacy and designing confidence-enhancement intervention programs to prevent social withdrawal behaviors among adolescents.